2019
DOI: 10.1093/jas/skz019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing of weaning on energy utilization in primiparous beef cows and post-weaning performance of their progeny1

Abstract: Early weaning is used to minimize cow nutrient requirements in situations where feed inputs are scarce or expensive. For many years, maintenance energy requirements have been assumed to be 20% greater in lactating compared with non-lactating beef cows. While not well established, maintenance energy requirements are thought to be greatest in primiparous cows and to decline with age. Consequently, early weaning primiparous cow–calf pairs should improve overall efficiency, particularly in situations where mid-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
3
9
0
2
Order By: Relevance
“…The same study found that efficiency ratios were greater for Angus/Hereford pairs compared with other breeds of cattle that had a greater genetic propensity for growth and milk production. Similarly, Wiseman et al (2019) found for traditionally weaned and early weaned primiparous Angus and Hereford × Angus pairs, efficiencies were 40.2 and 37.0 g of calf gain to total pair energy intake, respectively. It is important to note that both Jenkins et al (1991) and Wiseman et al (2019) offered ration ad libitum to calves while calf feed intake was restricted in the current experiment.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…The same study found that efficiency ratios were greater for Angus/Hereford pairs compared with other breeds of cattle that had a greater genetic propensity for growth and milk production. Similarly, Wiseman et al (2019) found for traditionally weaned and early weaned primiparous Angus and Hereford × Angus pairs, efficiencies were 40.2 and 37.0 g of calf gain to total pair energy intake, respectively. It is important to note that both Jenkins et al (1991) and Wiseman et al (2019) offered ration ad libitum to calves while calf feed intake was restricted in the current experiment.…”
Section: Discussionsupporting
confidence: 58%
“…It is possible that potential differences in maintenance requirements due to age are diluted in the current experiment because 2- and 3-yr-old cows were comingled. For example, in a previous study using similar techniques and a similar diet, Wiseman et al (2019) reported maintenance requirements of 107 kcal ME/kg BW 0.75 in primiparous cows from the same herd.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations